Անձի սոցիալամետ վարքագծում շփումը որպես նրա սոցիալական կապիտալի կուտակում - Անատոլի Սվենցիցկի; Իրինա Կուզնեցովա (ՀՀ ԳԱԱ հրատ.)
В статье рассматриваются проблемы общения в просоциальном поведении личности и приумножение ее социального капитала. This article considers communication issues of pro-social behavior of individuals and the growth of the social capital connected with it.
Keywords: Social Sciences; Sociology